Corporate social responsibility and competitiveness: a study of Brazilian multinationals - Melo,Mary Fernanda de Sousa de (2022)
Abstract Paper aims This study aims to analyze the relationship between the corporate social responsibility (CSR) strategy and competitiveness, considering the moderating effect of the governance mode on CSR actions. Originality This study sheds some light on a tendency towards the proactivity in terms of CSR of Brazilian Multinationals. They also present collaborative governance mode more frequently to conduct CSR actions. Research method In order to reach the research objective, a survey research was carried out in 144 Brazilian Multinationals and SmartPLS was used to conduct partial least square-structural equation modeling analysis. Main findings The results indicated that there is a positive relationship between CSR and competitiveness. Regarding the CSR governance mode, the adoption of different governance modes depending on the characteristics of the CSR action developed. Implications for theory and practice This paper contributes to the literature, since Latin America, especially Brazil, still lacks research that analyzes their CSR practices and establishes relationships with other organizational objectives, such as competitiveness.